BIOCHEMICAL EVALUATION OF CHRONIC CONSUMPTION OF MONOSODIUM GLUTAMATE ON LIVER OF WISTAR ALBINO RATS - THANGACHI, SURENDRA BABU; MOKHASI, VARSHA SRIRAM; CHENOLY, SHABINA KOMATH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of this study was to determine if there were any harmful effects of monosodium glutamate (MSG) on the liver of Wistar albino rats chronically at three different doses, namely, low, mid, and high doses equivalent to human consumption doses in developing countries. Methods: The Wistar albino rats (n=24) were divided into four groups, namely control, Low dose MSG (180 mg/kg), Mid dose MSG (360 mg/kg), and High dose MSG (720 mg/kg). At the end of the experimental period (120 days), animal blood was collected retro-orbitally to analyze the liver enzymes such as aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), Total protein, Albumin, and Total Bilirubin in blood serum. Lipid profiles, namely, Triglycerides, low-density lipoprotein (LDL), high-density lipoprotein (HDL), and Total cholesterol were subjected to analysis using blood serum. Results: Significant increase (p<0.05) in AST, ALT, ALP, and total bilirubin in serum of MSG induced low, mid, and high dose groups when compared to control group were recorded. There was a significant increase (p<0.05) in LDL, decrease in HDL, increase in total cholesterol and triglycerides of MSG-induced animal groups. Conclusion: The effects of MSG on serum liver enzymes and lipid profiles in this present animal study were not severely alarming even though the dosage was chronic which opens further discussion on the controversies revolving around MSG.